Fibroblast activation protein inhibitor-positron emission tomography in aortitis: fibroblast pathology in active inflammation and remission - Röhrich, Manuel; Rosales, Juan J; Hoppner, Jorge; Kvacskay, Peter; Blank, Norbert; Loi, Lisa; Paech, Daniel; Schreckenberger, Mathias; Giesel, Frederik L.; Kauczor, Hans-Ulrich; Lorenz, Hanns-Martin; Haberkorn, Uwe; et al. (Rheumatology, 2024)
Epigenetically modified fibroblasts contribute to chronicity in inflammatory diseases. Reasons for the relapsing character of large vessel vasculitis (LVV) remain obscure, including the role of fibroblasts, in part due to limited access to biopsies of involved tissue.68Ga FAPI-46 (FAPI)-PET/CT detects activated fibroblasts in vivo. In this exploratory pilot study, we tested the detection of fibroblast activation in vessel walls using FAPI-PET/CT in LVV with aortitis.Eight LVV patients with aortitis and eight age- and gender-matched controls were included. The distribution of FAPI uptake was evaluated in the aorta and large vessels. FAPI-uptake was compared with MRI inflammatory activity scores. Imaging results were compared with clinical parameters such as serum inflammatory markers, time of remission and medication.Three aortitis patients were clinically active and five in remission. Irrespective of activity, FAPI uptake was significantly enhanced in aortitis compared with controls. Patients in remission had a mean duration of remission of 2.8 years (range 1-4 years), yet significant FAPI uptake in the vessel wall was found. In remitted aortitis, MRI inflammatory scores were close to be negative, while in 4/5 patients visually identifiable FAPI uptake was observed.This pilot feasibility study shows significant tracer uptake in the aortic walls in LVV. FAPI positivity indicates ongoing fibroblast pathology in clinically remitted LVV.
Gesehen am 22.01.2025